Visualization of West Sumatra Ocean Surface Based on Topex/Poseidon, Jason-1 and Jason-2 Sattelites Data - Khasanah, Isna Uswatun (-)
This research attempts to monitor West Sumatra ocean surface based on data from satellite altimetry. Altimetry satellite data used is the Sea Surface Height (SSH) Data and Sea Level Anomaly (SLA). Satellite altimetry data processing are complex, include post processing, disposal of data mainland and an empty data as well as the disposal of data outliers. In this study, the global test used has a 99% level of confidence of the data. The quality of the data where the sea surface waters of West Sumatra of multi-satellite altimetry has a good quality of about 90%. Value SSH waters of West Sumatra after correction of missing data and data residing on the mainland ranging between -37 to -7 m. Geoid undulation value EGM96 West Sumatra ranged between -36 to 9. While the value of the SLA in the waters of West Sumatra ranged from -5.5 to 6 m.